Degradation of Reactive Blue 19 (RB19) by a Green Process Based on Peroxymonocarbonate Oxidation System - Thi Bich Viet Nguyen; Ngan Nguyen-Bich; Ngoc Duy Vu; Hien Ho Phuong; Hanh Nguyen Thi (Journal of Analytical Methods in Chemistry)
The effectiveness of peroxymonocarbonate (HCO4−) on the degradation of Reactive Blue 19 (RB19) textile dye was investigated in this study. The formation kinetics of HCO4− produced in situ in a H2O2−HCO3− system was studied to control the experimental conditions for the investigation of RB19 degradation at mild conditions. The effects of metallic ion catalysts, the pH, the input HCO3− and Co2+ concentrations, and UV irradiation were studied. The obtained result showed that Co2+ ion gave the highest efficiency on accelerating the rate of RB19 degradation by the H2O2–HCO3− system. In the pH range of 7–10, the higher pH values resulted in faster dye degradation. The reaction orders of the RB19 degradation with respect to Co2+ and HCO3– were determined to be 1.2 and 1.7, respectively. The UV irradiation remarkably enhanced the radical formation in the oxidation system, which led to high degradation efficiencies. The COD, TOC removal, and HPLC results clearly revealed complete mineralization of RB19 by the H2O2−HCO3−−Co2+ system.